A novel heptapeptide derived from Crassostrea gigas shows anticoagulant activity by targeting for thrombin active domain. (1st January 2021) - Cheng, Shuzhen; Tu, Maolin; Liu, Hanxiong; An, Yue; Du, Ming; Zhu, Beiwei
Highlights: Pepsin hydrolysate of oyster showed strong anticoagulant activity. P-3-CG prolonged the activated partial thromboplastin time significantly in vitro/vivo . P-3-CG decreased the mice mortality and reduced risk of thromboembolism in lung. Lys7 of P-3-CG competed with fibrinogen for binding thrombin S1 pocket. Abstract: A novel food-derived anticoagulant heptapeptides (P-3-CG) was isolated and characterized from oyster ( Crassostrea gigas ) pepsin hydrolysate. P-3-CG competed with fibrinogen against thrombin active domain by a spontaneous and exothermic reaction which was entropically driven. The residue Lys7 of P-3-CG anchored thrombin S1 pocket strongly, which inhibited fibrinogen binding to the thrombin, then blocked the conversion of fibrinogen to fibrin. The fibrinogen clotting time was prolonged to 27.55 s, and the reciprocally authenticated results of dynamic light scattering and scanning electron microscope further explained for fibrinogen clotting time extension. Inhibition of amidolytic activity of thrombin was affected significantly by reaction time and P-3-CG concentration. Furthermore, P-3-CG prolonged activated partial thromboplastin time significantly in vitro/vivo, and decreased the mortality which was confirmed by pulmonary pathological slide results. The obtained results demonstrated that P-3-CG may potentially serve as an alternative food-derived anticoagulant peptide that could be utilized for thrombosis prevention.